Interculturality in Language Teacher Education - Autores, Varios (Programa Editorial Universidad Del Valle, 2023)
The desire to develop more intercultural focused language teaching and learning has grown significantly and to date there has been a lot of attention given to theoretical issues around the nature of interculturality and what it means for language education, and also around the educational practices of intercultural language teaching and learning.